Pengaruh Harga, Kualitas Produk, Dan Citra Merek Terhadap Keputusan Pembelian Produk Breadtalk - Laurencia Angela Indarto; Stephanie Astrid Ayu (BIP's JURNAL BISNIS PERSPEKTIF, 2022)
This study is a quantitative study that aims to determine the effect of price, product quality, and brand image on purchasing decisions for BreadTalk products at the Galaxy Mall Surabaya BreadTalk Outlet. The sampling method is purposive sampling using questionnaires distributed to 75 respondents who are consumers of BreadTalk products who are 17 years old and over and have bought BreadTalk products. The results of the validity test show that all statement items are declared valid with a calculated r value > r table 0.2272. The results of the reliability test showed that all variables were declared reliable with the value of Croanbach's alpha > 0.6. The normality test showed that the data were normally distributed with a significance value of Asymp. Sig (2-tailed) of 0.200 is greater than 0.05. The multicollinearity test shows that this regression model does not experience multicollinearity because the tolerance value is > 0.10 and the VIF value is < 10. The heteroscedasticity test shows that this regression model does not experience symptoms of heteroscedasticity because the plot does not form a regular pattern. Multiple linear regression test produces the formula Y = 4.642 + 0.122 X1 + 0.507 X2 + 0.580 X3. The coefficient of determination shows that the independent variable provides a moderate contribution of 0.401 or 40.1% to the purchasing decision variable. The t-test in this study resulted in the price variable (X1) on purchasing decisions (Y) resulting in a t-count value of 0.606 < t table 1.99394 with a significant level of 0.546> 0.050 meaning that the price had no effect on purchasing decisions, the product quality variable (X2) on purchasing decisions (Y) produce a t-count value of 3.480 > t-table 1.99394 with a significant level of 0.001 <0.050 meaning that product quality has a significant effect on purchasing decisions, the brand image variable (X3) on purchasing decisions (Y) produces a tvalue of 3.204 > ttable 1.99394 with a significant level of 0.002 < 0.050 meaning that brand image has a significant effect on purchasing decisions.